If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(-3x + 4) + 3x = 42 Reorder the terms: -2(4 + -3x) + 3x = 42 (4 * -2 + -3x * -2) + 3x = 42 (-8 + 6x) + 3x = 42 Combine like terms: 6x + 3x = 9x -8 + 9x = 42 Solving -8 + 9x = 42 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + 9x = 42 + 8 Combine like terms: -8 + 8 = 0 0 + 9x = 42 + 8 9x = 42 + 8 Combine like terms: 42 + 8 = 50 9x = 50 Divide each side by '9'. x = 5.555555556 Simplifying x = 5.555555556
| -12x^2-2x=4 | | sa+3b=7a | | (3a+5)(4a)= | | 0.2x-4=0.4+4 | | P=20-4q | | 0.30x=0.25x+1 | | 6+12x+36=7x+30+6x | | (2x-7)-(3x+5)=5(x-3) | | f(x)=x^4-9x^2+18 | | 8a=4b-20 | | 6-10x=0 | | 2x+66=5x+9 | | (x+2)*(5-3x)= | | C^2-15c-54=0 | | 4(x+6)-x(x+6)=0 | | lg(2x)=4.5 | | 4(n-3)-3n=1+2 | | cos^2x+5cosx=1 | | 15x-17=22 | | 10+7f=8f | | 2x+18=-3y | | 3*(5*x-7)+2*(2*x+17)=5*(3*x-4)+37 | | (3y-5)(8-y)=0 | | 4(x)=3x-1 | | X^2+x=0.24 | | 3(1)-2(6)=9 | | 5x+1=-16 | | 6(y+2)=-3(6y-1)+6y | | 13X=10X-9 | | Y=-x(x-2) | | 3(1)+2(6)=9 | | 3x^2+5x-2y^2=0 |